Concepção de um equipamento para transporte pneumático de semente em implementos agrícolas - Kurz, Valter Odair (2023)
The expansion of the agricultural machinery and implements sector is increasing every year, because due to climate change, the window (time) for planting has reduced every year and farmers seek to reduce the time in which the seeders are stopped, taking advantage of the maximum period of planting. Based on this information, this work presents the development of a pneumatic system of suction and/or overpressure for supplying seeders, from agricultural carts and/or trucks and thus presents an innovation in the supplying of seeders, being compact, practical, safe. and ergonomic. The development of the project was based on the methodology proposed by Norton (2013), divided into three main stages: in the first stage, presentation of the initial planning for the development of the concept, with market and consumer analysis, assessing the real need of the market, as well as defining the ideas for the development of the project; in the second stage, the solutions were combined, as well as the evaluation and definition of the solution to be used; in the third and last stage, called detailed design, the components used for the development of the project are presented, as well as the definition of which items can be produced and recommended suppliers, thus allowing the concept of a product with the possibility of progressing to a definitive project , prototyping and large-scale manufacturing. The study presented made it possible to document the design of equipment for supplying a seeder through a pneumatic system, which aims to improve the quality of work of the farmer, in addition to enabling a supply with safety and speed.